Evaluations of phylogenetic proximity in a group of 67 dogs with osteosarcoma: a pilot study - Fabrizio, di Virgilio; Johan, Caraty; Roy, Hassoun; Annick, Hamaide; Pierre, Meheust; Frédéric, Farnir (Journal of Veterinary Healthcare, 2020)
Aim of the Research The aim of this study is to analyze a group of dogs of different breeds affected by osteosarcoma (OSA), to document any prevalence of this primary bone neoplasia in breeds that are phylogenetically close and to help with further research human medicine, as a model of study for prevalence and epidemiology of human OSA in multiple populations. Study Design Pilot study from two canine surgery databases between 2002 and 2013. Materials and Methods Breeds were classified in groups based on their phylogenetical proximity. Differences in prevalence of OSA between breeds and groups were evaluated with a permutation test. For each breed and each group, a ranking was made by calculating 95 % confidence intervals and counting the no-overlapping between breeds and groups. The relation between the dogs’ heights and the prevalence of OSA was analyzed using a logistic regression between the disease status and dog size. Results A total of 67 dogs with OSA, in 26 different breeds were included. Ten breeds were overrepresented and, the majority of these, were classified in 2 predisposed groups phylogenetically close to each other. The prevalence of OSA was associated with the dogs’ height within predisposed breeds, but, in general, taller breeds were not the most affected. Conclusions and Clinical Relevance In this study, despite the small number of dogs, we observed that the most commonly affected breeds with OSA are phylogenetically closely related. This highlights the importance of genetics in the aetiology of canine OSA . In this preliminary study, indications are given on breeds, samples and genome locations to be further investigated. This could allow identification of pathogenic alleles in dogs, and potentially in humans. Furthermore this pilot research can represent a model of epidemiologic study of human OSA.
Keywords: Breed prevalence; canine model; canine osteosarcoma; OSA; OSA epidemiology.